If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5x + -11) + 2(3x + 5) = 0 Reorder the terms: -1(-11 + 5x) + 2(3x + 5) = 0 (-11 * -1 + 5x * -1) + 2(3x + 5) = 0 (11 + -5x) + 2(3x + 5) = 0 Reorder the terms: 11 + -5x + 2(5 + 3x) = 0 11 + -5x + (5 * 2 + 3x * 2) = 0 11 + -5x + (10 + 6x) = 0 Reorder the terms: 11 + 10 + -5x + 6x = 0 Combine like terms: 11 + 10 = 21 21 + -5x + 6x = 0 Combine like terms: -5x + 6x = 1x 21 + 1x = 0 Solving 21 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 1x = 0 + -21 Combine like terms: 21 + -21 = 0 0 + 1x = 0 + -21 1x = 0 + -21 Combine like terms: 0 + -21 = -21 1x = -21 Divide each side by '1'. x = -21 Simplifying x = -21
| 8x^2-9x-8=0 | | 742=7x+4x+2x | | M-7=-20 | | 5z^2+11z+2= | | 5/6=5/6x | | (2+2)+5=x | | 13/6=5/6x | | 3x+2=11.5 | | d^-5m/14n^6 | | 26x-7-18x+3=21-4-13x+16 | | x^2-2(2a-1)x+a=0 | | 2t^2-46t+22=0 | | -2t^2+46t-22=0 | | 4k^2-4k+1=9 | | (4a+3b)(a+2b)=(3a+b-2) | | (4a+3b)(a+2b)= | | 2x^2-(2m-1)x+2m+1=0 | | x+-2+3=-2 | | 3(u-3)-4i=11 | | X^2+3x=56 | | -4/x | | -4/x=2/3 | | (10-27/x)1.1x | | (4x-2y)+(x+y)= | | 1+x-2+5-3=0 | | -x^3-3*x^2-1=0 | | 2*Sin^2(x)+3*cos(x)-2=0 | | 2/9×3x=x-56 | | (x-4)(x^3-1)(16+x)=0 | | (x^2-4)(4x+1)=0 | | (x+2)(x-2)(4x+1)=0 | | (x+7)(x-7)(4x-1)=0 |